Translation strategies and representation of meaning in idioms in Three Kingdoms - Khoo, Yen Loo (2018)
The target materials of this research are the idioms used in San Guo Yan Yi (Three Kingdoms), written in classical Chinese by Luo Guanzhong and its corresponding English translation by Moss Roberts. Idioms are fixed expressions embedded with cultural elements, which often pose difficult to translators. This study aims to compare the differences in the translation enacted from the use of the same idiom found in different context found throughout the original novel. Cresswell‘s (2014) and Aldebyan‘s (2008) qualitative methodologies are applied for the data collection and analysis. All idioms that were utilized more than six times in the original novel were analyzed. There are two distinct phases involved in the analysis. The first involved identifying the translation strategies used. The frameworks of analysis used for this phase of the study involved identification of translation strategies following Vinay and Darbelnet (2004) and Baker‘s (1992) suggestions on strategies for translating idioms. The second phase of the study adopted the transitivity system in the Systemic Functional Linguistics (SFL) approach to language use by Halliday and Matthiessen (2014). In this phase of the study, the representation of the idioms in the source and target texts are examined closely to describe the literal lineament in translated texts. These processes examined provide an insight to fathom Roberts‘ words selection on his translation of idioms or Chengyu. The results show that paraphrasing is the strategy that is applied the most. It is used to rephrase the conveyed messages in the idioms. This is to explain the intended meanings of the idioms in order to ensure the way of conveying ideas are comprehensible. The use of direct literal translation is the second most frequent strategy used and it helps to retain the cultural elements or beauty of the source language. The second phase of the investigation reveals that the idioms that were reiterated for numerous times in the novel were presented differently to accommodate the need of the contexts. These translated idioms were grouped into six different processes upon comparisons between the idioms in the source texts and the translated words or phrases. The analysis showed difference in distinct word selection, for the purpose of pertinent context presentation and message delivery. Ultimately, the analysis in this study strives to offer insights on idiom translation methodologies by illustrating the silhouette of word concordances that vary with dissimilar circumstances.